Determinants of information system quality and data quality in management accounting - Thorsten Knauer; Nicole Nikiforow; Sebastian Wagener (Journal of Management Control, 2020)
Data quality is critical to adequately perform management accounting (MA) tasks, and information systems (IS) provide the data for the MA domain. However, IS can vary vastly across firms, which may influence the basis for rational decision making (i.e., data quality). This study therefore aims to investigate the impact of IS quality on data quality in MA and to analyze the determinants that can influence IS quality in MA. We conduct a cross-sectional survey among 143 medium-sized and large firms. Based on a structural equation model, we predict and find that IS quality significantly affects management accounting data quality (MADQ). Company's IT investments, internal and external IT knowledge, innovative technologies, and data source variety are significantly associated with IS quality in MA and in turn indirectly affect MADQ. This study highlights the importance of IS quality for management accountants' practice and simultaneously provides new insights regarding the efficacy of selected determinants of IS quality.
Keywords: M15; M41; 330; Data quality; Information systems; Information technology; Management accounting; System quality